Examining the framing of ‘COVID-19 vaccines’: A corpus-based investigation of Malaysian newspapers - Norasyikin Abdul Malik; Mohamad Syafiq Ya Shak; Nurul Ain Hasni (Studies in English Language and Education, 2023)
The widespread dissemination of misinformation or the ‘infodemic’ surrounding COVID-19 poses a significant challenge as the virus continues to spread globally, compounded by the reluctance of many individuals to accept ‘COVID-19 vaccines’. While existing research has predominantly explored how the media framed the disease, its psychological impact, and the presence of disinformation in its messaging, limited attention has been given to the portrayal of ‘COVID-19 vaccines’ in the media and their reception among the general population. This study employs a corpus-based methodology to examine the framing of ‘COVID-19 vaccines’ within a specific English Malaysian newspaper corpus. The data for analysis was gathered through the compilation of news reports from The Star, one of the nation’s primary English newspapers. The analysis showed that the vaccine was positively framed and correlated with keywords like ‘special’, ‘effective’, and ‘important’, as well as with keywords indicating its importance to one’s health and the masses. However, two negatively connoted keywords were also used to describe the act of immunisation. This study’s findings can encourage informed decision-making on COVID-19 vaccination by dispelling unwarranted fears. Positive news coverage can boost confidence and prevent panic while mitigating negative emotions and risk perceptions. These findings can help media practitioners better frame vaccine-related issues in their writings and understand how the public perceives them.